Towards a Sociological Model of Corporate Entrepreneurship - Dingsdale, Simon (2008)
The primary purpose of this study is to establish a sociological grounding for the field of Corporate Entrepreneurship (CE) through the development of an organic sociological model. I argue that there are four key problems underlying the CE literature 1) no unifying theoretical base 2) no multi-dimensional, organic model 3) no multi-dimensional analysis 3) no easily implementable model and 4) no identification of critical antecedents. Scholars have failed to understand that without a unifying theoretical base, it is difficult to produce a set of guidelines for business management to follow. A lack of theoretical grounding has lead to a narrow research field making pragmatic implementation of the concept extremely difficult. I argue that CE should be studied as a social phenomenon, and that the application of sociological theory can help reconcile the fundamental problems that run deep within the field. These problems are mirrored in the debates that rage within sociological theory. The dichotomy between 'macro/micro' and 'agency/structure' mirrors many of the fundamental difficulties facing CE research. While the field of CE itself cannot provide answers to this fundamental divide, sociological theory and debate can. I acknowledge that it is impossible to model CE based on a universally accepted theory, because there is no such theory. However, while to establish a multi-dimensional model of CE may appear to be a near impossible task from the outset, I argue the application of a sociological perspective can go a long way toward this goal.